Reliability and validity of the Japanese version of the ADL-focused Occupation-based Neurobehavioural Evaluation (A-ONE J): Applying Rasch analysis methods. Issue 1 (June 2019) - Higashi, Yasuhiro; Takabatake, Shinichi; Matsubara, Asako; Nishikawa, Koji; Shigeta, Hiroto; Árnadóttir, Guðrún
Background/objective: The ADL-focused Occupation-based Neurobehavioral Evaluation (A-ONE) can be used to evaluate both performances of activities of daily living (ADL) tasks and neurobehavioural problems that interfere with ADL task performance among clients with neurological disorders. Research studies have demonstrated acceptable psychometric properties of the original version of the A-ONE as well as the Rasch analysed version. The aim of this study was to examine the reliability and validity of the Japanese version of the A-ONE (A-ONE J). Methods: Rasch analysis was performed on data obtained from eight different hospitals in Japan on performances of 150 individuals diagnosed with a stroke based on the functional independence (FI) scale items. The rating scale structure was investigated and internal validity and reliability were examined. Unidimensionality of the items was examined by mean square infit values and principal component analysis of residuals. The targeting between person ability and item difficulty was explored, as well as the separation reliability. Finally, psychometric values and item difficulty hierarchies obtained in this study were compared to the original Rasch analysis of the A-ONE. Results: The rating scale structure might be improved by collapsing two categories twice (from five categories to three categories). Unidimensionality of the items was obtained for 20 items. Targeting was acceptable, and separation reliability for item calibrations was high and acceptable for people. Conclusion/limitations: This study provides important information regarding the possibilities for revising the ordinal A-ONE J FI Scale, converting it into a unidimensional scale. Further study with increased and more diverse sample is needed.